3D/2D direct Z-scheme heterojunctions of hierarchical TiO2 microflowers/g-C3N4 nanosheets with enhanced charge carrier separation for photocatalytic H2 evolution. (August 2019) - Wang, Juan; Wang, Guohong; Wang, Xiao; Wu, Yao; Su, Yaorong; Tang, Hua
Abstract: Constructing a 3D/2D direct Z-scheme heterojunction is a practical way to promote charge separation for attaining efficient solar hydrogen production. In the present work, hybrid 3D TiO2 microflowers/2D g-C3 N4 nanosheets with a direct Z-scheme heterostructure is designed and fabricated through a hydrothermal and calcination process. The photocatalytic properties of the hybrid photocatalysts are evaluated by water splitting under solar light irradiation. The optimal ratio of g-C3 N4 in the hybrid is found to be 50% (wt), and the resulting TiO2 /g-C3 N4 composite shows the highest photocatalytic activity among the experimental samples, which is 7.7 and 1.9 times higher than that of bare g-C3 N4 and TiO2, respectively. The outstanding H2 production activity benefits from the synergistic effects of highly dispersed 3D TiO2 microflowers, extended photo-response to visible light through coordinating with 2D g-C3 N4 nanosheets and the strong coupling effect resulting from an efficient direct Z-scheme structure. Photoluminescence and photocurrent response results reveal that the photoinduced e − -h + pairs in this 3D/2D direct Z-scheme heterojunction can be separated efficiently, which also accounts for the obtained outstanding performance. Our results suggest that constructing a 3D/2D Z-scheme heterojunction in photocatalysts could be an efficient way to realize high speed solar H2 production. Graphical abstract: Image 10669